2020
DOI: 10.14814/phy2.14370
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine responsiveness is reduced in livers from trained mice

Abstract: The liver is the primary metabolic organ involved in the endogenous production of glucose through glycogenolysis and gluconeogenesis. Hepatic glucose production (HGP) is increased via neural‐hormonal mechanisms such as increases in catecholamines. To date, the effects of prior exercise training on the hepatic response to epinephrine have not been fully elucidated. To examine the role of epinephrine signaling on indices of HGP in trained mice, male C57BL/6 mice were either subjected to 12 days of voluntary whee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
(99 reference statements)
1
9
0
Order By: Relevance
“…Approximately 90% of endogenous glucose is produced by the liver system, which can maintain blood glucose balance by regulating gluconeogenesis, glycogenolysis, and other pathways. 61 , 62 Previous studies have shown that the inhibition of hepatic gluconeogenesis can improve blood glucose levels in patients with T2DM. 63 The liver is not only an important organ that is involved not only in the synthesis, decomposition, and metabolism of carbohydrates in the body to maintain blood glucose stability but also in the degradation, clearance, and glucose metabolism of INS.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 90% of endogenous glucose is produced by the liver system, which can maintain blood glucose balance by regulating gluconeogenesis, glycogenolysis, and other pathways. 61 , 62 Previous studies have shown that the inhibition of hepatic gluconeogenesis can improve blood glucose levels in patients with T2DM. 63 The liver is not only an important organ that is involved not only in the synthesis, decomposition, and metabolism of carbohydrates in the body to maintain blood glucose stability but also in the degradation, clearance, and glucose metabolism of INS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the increased glucose output during perfusion with adrenaline, especially in group T8, is probably explained by substrate increase (glycogen). The sensitivity of the catecholaminergic pathway does not seem to be altered by HIIRT, because the content of PKA, the intracellular agent of the glycogenolytic action of catecholamines (Dibe et al, 2020;Petersen et al, 2017), was unchanged.…”
Section: R a F Tmentioning
confidence: 95%
“…Liver glucose release comes from glycogenolysis (glycogen degradation) and gluconeogenesis -glucose synthesis from non-carbohydrate substrates, such as glycerol, several amino acids, pyruvate and lactate (Dibe et al, 2020;Hawley et al, 2014;Jensen & Richter, 2012;Mul et al, 2015;Rui, 2014;Spriet, 2014;Stark & Kibbey, 2014;Thyfault & Bergouignan, 2020;Trefts et al, 2015). Quantitatively, lactate is the major gluconeogenic precursor in any physiological circumstance (Stark & Kibbey, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Acute exercise stimulates adipose tissue lipolysis, with low/moderate exercise eliciting a 2 to 5-fold increase in circulating free fatty acids for use in substrate metabolism ( Havel et al, 1963 ; Ahlborg et al, 1974 ; Wolfe et al, 1990 ; Romijn et al, 1993 ; Ranallo and Rhodes, 1998 ; Burguera et al, 2000 ). Moreover, acute exercise also increases liver gluconeogenesis and hepatic glucose output via catecholamine release and sympathetic activity ( Dibe et al, 2020 ) which aligns with changes in glucose production with aging.…”
Section: Effects Of Aging and Exercise On Metabolismmentioning
confidence: 99%